"There's no acknowledgement of what this does to people": A qualitative exploration of mental health among parents of children with critical congenital heart defects. Issue 13 (13th March 2018) - Woolf‐King, Sarah E; Arnold, Emily; Weiss, Sandra; Teitel, David
Abstract : Aims and objectives: The purpose of this study was to explore the psychological impact of parenting a child with a critical congenital heart defect and the feasibility and acceptability of integrating psychological services into paediatric cardiology care. Background: Children with critical congenital heart defect are at an increased risk for long‐term behavioural, social and emotional difficulties. Data suggest that this risk is partially attributable to parental mental health, which is a stronger predictor of long‐term behavioural problems in congenital heart defect children than disease‐specific and surgical factors. Parental stress and mental health are thus important intervention targets, especially among high‐risk families. Design: This article presents data from a qualitative study with 25 congenital heart defect parents ( n  = 15) and providers ( n  = 10). Methods: Using thematic analysis, semi‐structured in‐depth interviews were transcribed and coded by the first and second author to identify major themes and subthemes. Results: Results of the interviews were organised into four major themes: (i) the psychological impact of parenting a child with critical congenital heart defect, (ii) factors that influence the psychological impact of parenting a child with critical congenital heart defect, (iii) how and when to psychologically support congenital heart defect parents and (iv) feasibility and acceptability of integrating psychological support into congenital heart defect care. Providers and parents endorsed the integration of mental health treatment into routine congenital heart defect care and identified several practical issues related to feasibility (e.g., funding and space) that should be considered prior to implementation. Conclusions: Parents of children with critical congenital heart defect need access to mental health services, and integrating these services into routine paediatric cardiology care is a novel and practical way for parents to receive the treatment they need. Relevance to clinical practice: Suggestions for how the field of paediatric cardiology could begin to integrate mental health services into congenital heart defect treatment are provided.